Oblicz (z działaniami):
[tex](\sqrt[3]{500}- \sqrt[3]{4} ) * \sqrt[3]{2} =\\ \sqrt{3} *(\sqrt{75} + \sqrt{48} )=\\ (\sqrt{20} + \sqrt{5} + \sqrt{125} + \sqrt{45} ) : \sqrt{5} =[/tex]


Odpowiedź :

Odpowiedź:

[tex](\sqrt[3]{500}-\sqrt[3]{4})*\sqrt[3]{2}=\sqrt[3]{500}*\sqrt[3]{2}-\sqrt[3]{4}*\sqrt[3]{2}= \sqrt[3]{1000}-\sqrt[3]{8}=10-2=8\\\\\\\sqrt{3}*(\sqrt{75}+\sqrt{48})=\sqrt{225}+\sqrt{144}=15+12=27\\\\\\(\sqrt{20}+\sqrt{5}+\sqrt{125}+\sqrt{45}):\sqrt{5}=\sqrt{4}+1+\sqrt{25}+\sqrt{9}=2+1+5+3=11[/tex]